Chase's Calendar of Events 2014. (New York : McGraw-Hill, 2014)
"4,000 notable birthdays, 1,400 historical anniversaries, 650 national and international holidays, 160 religious holidays, and thousands of additional days of note from all over the globe" -- Cover.
Spotlight on 2014 anniversaries and events -- Spotlight on the past: 1864, 1914, 1939, 1964, 1989 -- Spotlight on people -- Spotlight on 2014 events -- Calendar of events: Jan. 1 - Dec 31, 2014 -- Calendar information for the years 2014-2016 -- Looking forward: Future anniversaries and major events -- Perpetual calendar -- National days of the world for 2014 -- Selected special years1995-2014 -- Chinese calendar -- Wedding anniversary gifts -- World map of time zones -- Universal, standard, and daylight times -- Leap seconds -- Astronomical phenomena for the years 2014-2016 --Naming of hurricanes -- Some facts about the US presidents -- Some facts about the United States -- State and territory abbreviations: United States -- State governors; US senators; US Supreme Court -- Some facts about Canada -- Province and territory abbreviations: Canada -- Some facts about Mexico -- 2014 special months -- Presidential proclamations -- Major awards presented in 2012-2013.
Includes index.
Compatible with PCs running Windows XP and higher. Compatible with MACs OSX 10.7 and higher.
Keywords: Holidays -- United States; Holidays; Holidays; Almanacs; Directories